TEACHING A FOREIGN LANGUAGE USING EFFECTIVE TEACHING METHODS IN TECHNICAL (NON-LINGUISTIC) UNIVERSITIES - Badalova Luiza Kholmamatovna (Bright Mind Publishing, 2025)
This article analyzes and presents methods for teaching a foreign language in non-linguistic universities, which are widely used in pedagogy to create an effective learning process in the classroom. The article also provides lists of important queries and difficulties encountered by both new and seasoned educators to assist in determining what constitutes a practicum's necessary components.
Keywords: Method, efficiency, key concepts, foreign language teaching, contemporary teaching, techniques, non-linguistic (technical) university.